2022
DOI: 10.1093/ofid/ofac447
|View full text |Cite
|
Sign up to set email alerts
|

Creation and Internal Validation of a Clinical Predictive Model for Fluconazole Resistance in Patients With Candida Bloodstream Infection

Abstract: Background IDSA guidelines on candidemia recommend fluconazole as first-line therapy when the risk of fluconazole-resistance (fluc-R) is low. There is no method to estimate risk of resistance resulting in extended use of echinocandins and prolonged hospitalization. This study aimed to develop a clinical predictive model to identify patients at low risk for fluc-R where initial use of fluconazole or early step-down would be appropriate. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 29 publications
0
13
2
Order By: Relevance
“…Environmental spreading of resistant C. tropicalis strains was possible, according to previous reports on C. tropicalis and C. parapsilosis [ 6 , 28 ]. However, we have no direct evidence of patient-to-patient transmission, although the history of azole exposure was still a strong independent risk factor as in previous studies [ 12 , 13 ].…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Environmental spreading of resistant C. tropicalis strains was possible, according to previous reports on C. tropicalis and C. parapsilosis [ 6 , 28 ]. However, we have no direct evidence of patient-to-patient transmission, although the history of azole exposure was still a strong independent risk factor as in previous studies [ 12 , 13 ].…”
Section: Discussioncontrasting
confidence: 64%
“…Similarly, in China, fluconazole-resistant isolates increased from less than 10% in 2010–2012 to more than 30% in 2016–2017 [ 7 ]. Several studies reported the relationship between azole-resistant Candida infection and identified multiple risk factors including previous exposure to fluconazole and a history of bacterial bloodstream infection [ 12 , 13 ]. The description of C. tropicalis azole resistance was attributed to the four major mechanisms related to ERG11 mutations, ERG11 overexpression, alteration of membrane sterol composition, and increased expression of the efflux pump genes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The SENTRY Antifungal Surveillance Program reported a steady emergence of fluconazole-resistant species, with the highest rates of fluconazole-resistant in C. glabrata [11]. Regardless of Candida species, the risk of fluconazole resistance increases with suboptimal doses and up to 3-fold higher risk has been described with prolonged use [12]. The Centers for Disease Control and Prevention (CDC) listed fluconazole-resistant Candida species among the pathogens posing a serious threat to human health in its 2013 landmark report on antimicrobial resistance [13].…”
Section: Introductionmentioning
confidence: 99%
“…To the Editor —We read with interest the article by Rauseo et al [ 1 ] regarding the derivation and internal validation of a clinical predictive model for fluconazole resistance in patients hospitalized with candidemia. Their model consisted of 5 clinical parameters associated with fluconazole-resistant candidemia: older age, hematopoietic stem cell transplant (HSCT), myelodysplastic syndrome (MDS), azole exposure, and recent bacteremia.…”
mentioning
confidence: 99%
“…External validation of this model in an international cohort is desirable before its clinical implementation, especially considering previous difficulties validating similar risk models in invasive candidiasis [ 2 ]. We aimed to assess the generalizability of Rauseo et al's [ 1 ] model to an Australian context and explore clinical factors predictive of fluconazole resistance in an Australian setting.…”
mentioning
confidence: 99%